Bianchi type III string cosmological models for perfect fluid distribution in general relativity - Amirhashchi, Hassan; Zainuddin, Hishamuddin; Hassan, Jumiah; Mohamed Kamari, Halimah (American Institute of Physics, 2009)
Some geometrical aspects of Bianchi type III space‐time are investigated. This is followed by the study of Bianchi type III string cosmological models with perfect fluid distribution of matter.